ATRIBUT INOVASI LAYANAN ADMINISTRASI MELALUI SI D’nOK DI KOTA SEMARANG - Karina Putri Widiantari, Bernadeta; Sunu Astuti, Retno; Kismartini, Kismartini (Journal of Public Policy and Management Review, 2024)
The SI D'nOK (Semarang City Population Online Document Information System) application is an innovation initiated by the Semarang City Population and Civil Registration Office to overcome various problems related to population administration services. This mobile-based innovation can be accessed through smartphones flexibly. This study was conducted with the aim of analyzing the attributes of application-based service innovation in the successful implementation of population administration as well as the inhibiting factors of population administration application based service innovation in Semarang City. This application is analyzed using the theory of innovation attributes with several phenomena such as relative advantage, compability, complexity, triability, and observability. In addition, the inhibiting factors of SI D'nOK innovation were analyzed using phenomena such as reluctance to close failed programs, risk aversion culture, over reliance on high performers, existing technology but hampered by culture and organizational arrangement, inability to face the risk of change, and value congruence. This research was conducted using descriptive qualitative methods, with research subjects taken by purposive sampling, namely several agencies and the community. The results showed that, first, relative benefits, benefits of convenience of use compared to manual counters, cost and time benefits have been fulfilled. Next, the suitability of this service innovation is enough to answer the needs of the community, but it still needs to develop its features. Third, complexity, there are still human resource limitations and network problems found by users. Furthermore, the possibility of being tried and ease of observation has been carried out regularly, but there are still few people who know the existence of the SI D'nOK application. The inhibiting factor of this service innovation lies in the inability to face risks and changes due to network barriers that have not been fully resolved and a culture of risk aversion because adequate human resources have not been maximized.